2002
DOI: 10.1046/j.1365-201x.2002.01011.x
|View full text |Cite
|
Sign up to set email alerts
|

Cardiomyocyte contractility and calcium handling partially recover after early deterioration during post‐infarction failure in rat

Abstract: The aim of the study was to determine whether progression of heart failure is associated with deterioration of cardiomyocyte function. Cell dimensions, contractility and calcium transients were measured in cardiomyocytes isolated from the left ventricle of female Wistar rats 1, 4, and 13 weeks after coronary artery ligation or sham-operation. Relative cardiomyocyte shortening decreased from 26% in controls to 11% 1 week after myocardial infarction and recovered to 18 and 20% after 4 and 13 weeks, respectively.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 35 publications
1
17
0
Order By: Relevance
“…Rat model of chronic post-infarction cardiomyopathy was used as it is a well established reproducible model of dysfunction. 22,23 Syngeneic rat strains avoid the need for immunosuppression after abdominal transplantation. Therefore, male Lewis rats (200–300 g) were used for all experiments.…”
Section: Methodsmentioning
confidence: 99%
“…Rat model of chronic post-infarction cardiomyopathy was used as it is a well established reproducible model of dysfunction. 22,23 Syngeneic rat strains avoid the need for immunosuppression after abdominal transplantation. Therefore, male Lewis rats (200–300 g) were used for all experiments.…”
Section: Methodsmentioning
confidence: 99%
“…19 Cardiomyocytes isolated from HF animals show dysfunctional excitation, Ca 2ϩ handling, and contraction; abnormal cellular structure and architecture; and a pathological hypertrophy that is greater than the physiological hypertrophy observed after exercise training in healthy counterparts. 20,21 These changes explain the reduced ability of the cardiomyocyte and the whole heart to perform beat-to-beat contractile work. Importantly, they are also prone to positive modulation by exercise training; in fact, regular aerobic exercise training has been demonstrated to correct and reverse at least some of the pathological alterations in the cardiomyocyte and more so after high-intensity exercise training programs at approximately 90% of V .…”
Section: Animal Models Of Heart Diseasementioning
confidence: 98%
“…Although stroke volume is acutely regulated by extracardiac factors such as venous return, neurohormonal regulation, and afterload, previous studies identified significant correlation between contractile function of isolated myocytes and integrated in vivo function, indicating a contribution of intrinsic myocardial properties as well at both the molecular 29 and cellular levels. 6,18,30 Both statistical correlation and parallel time courses indicate that changes in cardiomyocyte size and function are likely to account for the changes in V O 2 max. Because of the high internal correlations between different measures of cardiomyocyte size and function, it is to be expected that only 1 or 2 prove to be significant in multivariate regression analysis.…”
Section: Cardiomyocyte Contractile Capacitymentioning
confidence: 99%